Altar dedicated to St. Anthony, the patron saint of Deussua - Mumbai Archive Project (Jio Institute, 2024)
The altar is dedicated to St. Anthony, the patron saint of Deussua, after whom the club is named. The Latin phrase praebe filii cor tumm written on the shrine with portraits of Jesus and Mary (on the left) means ‘My Son, give me thy heart.’ The Latin phrase domus mea doums orationis on the central arch means ‘My house is a house of prayer.’ The Latin phrase petite et acepietis on the arch with a portrait of the Madonna and child (on the right) means ‘ask and you shall receive.’ The altar has been illuminated with lights during Christmas.